Activation Studies on a Human Prothrombin Variant: Prothrombin Barcelona - Benarous, R.; Rabiet, M.J.; Labie, D.; Josso, F. (Thrombosis and Haemostasis, 1977)
Prothrombin Barcelona tested in the plasma from homozygous patients is characterized by a functional defect (5% activity by a one-stage assay) contrasting with a normal prothrombin concentration found by immunochemical assay.This low biological activity is the expression of a very slow rate of conversion of prothrombin into thrombin. It may be postulated that the abnormal kinetics of conversion of this variant might involve an inhibition of one of the proteolytic cleavages responsible for the activation process. To test this hypothesis, purified normal and abnormal prothrombins were submitted to proteolysis with factor Xa and thrombin, either with or without protease inhibitors. Prothrombin cleavage was checked at various times by SDS gel electrophoresis.In the presence of factor Xa, conversion of normal prothrombin into intermediate II started within 30 min and was almost complete within two hours. In the same conditions, conversion into intermediate II of prothrombin Barcelona was only initiated after two hours. Conversely upon treatment of both prothrombins with thrombin, a slight delay in the formation of intermediate I was observed with prothrombin Barcelona, this formation being nevertheless complete after one hr.In conclusion, the abnormal activation of prothrombin Barcelona seems mainly due to a decreased and delayed formation of intermediate II.